1981
DOI: 10.1002/elps.1150020507
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization kinetics of polyacrylamide gels. III. Effect of catalysts

Abstract: The kinetics of photopolymerization, in presence of riboflavin or riboflavin-5'-phosphate (FMN), have been studied either spectrophotometrically, at 283 nm, or chemically, by titrating unreacted double bonds with permanganate. The two sets of data are in good agreement and suggest that at least 8 h of light exposure are needed to ensure 95 % conversion of monomers into polymer. Up to now, it was generally accepted that photopolymerization should proceed for 1 h. It is not necessary to prolong light exposure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…Thus, there would be a distinct advantage in switching from persulfate-to riboflavin-initiated polymerization. However, after an extensive study, we had also found riboflavin catalysis, as commonly performed in biochemical laboratories (with 12 W neon bulbs for 1 h), to be a poor process, resulting in low conversion of monomers into the growing chain and producing gels that were too soft and gluey [12]. Thus, we had in fact discour-aged scientists from using riboflavin catalysis.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, there would be a distinct advantage in switching from persulfate-to riboflavin-initiated polymerization. However, after an extensive study, we had also found riboflavin catalysis, as commonly performed in biochemical laboratories (with 12 W neon bulbs for 1 h), to be a poor process, resulting in low conversion of monomers into the growing chain and producing gels that were too soft and gluey [12]. Thus, we had in fact discour-aged scientists from using riboflavin catalysis.…”
Section: Introductionmentioning
confidence: 89%
“…Under standard conditions, the gels were made to contain 100 WM dye, 1 mM reducer and 50 WM oxidiBy this term we mean the time which elapses between the start of illumination of the initial monomer mixture and the start of gelation. In previous publications [12], this was termed 'lag time', but in reality there is a minute but important difference between the gel point and the 'lag time', the former being somewhat longer than the latter (towards the end of the lag time,viscosityrises abruptlyuntil gelation occurs). The onset of gelation is measured by turning sealed tubes of monomer mixtures upside down until no more liquid movement occurs.…”
Section: Photopolymerizationmentioning
confidence: 96%
See 1 more Smart Citation
“…These systems are not without drawbacks, since uranium is toxic and weakly radioactive. On the other hand, riboflavin-based polymerizations are not reproducible and often lead to poorly polymerized gels [16]. This is why we decided to test the recently described photopolymerization system based on methylene blue [17], which does not contain high amounts of oxidizing material and was shown to give excellent polymerization efficiencies at acidic pH, where the other systems fail [18].…”
Section: Introductionmentioning
confidence: 99%
“…The limiting factor in increasing the percentage of total monomer however is the longer preparation time due to the low solubility of the bis powder and also formation of the crystals. It has been reported that low temperature water is not an ideal solvent for bis (Righetti et al 1983), therefore to help dissolve the bis powder the gel solution should keep heated during magnetic stirring. It was observed on top of the gel that was prepared using 9% of total monomers crystalline salt was formed one week after preparation.…”
Section: Applicationsmentioning
confidence: 99%